Acupuncture and related interventions for carpal tunnel syndrome: systematic review. (January 2020) - Wu, Irene XY; Lam, Victor CK; Ho, Robin ST; Cheung, William KW; Sit, Regina WS; Chou, Li-Wei; Zhang, Yan; Leung, Ting-Hung; Chung, Vincent CH
Objective: To synthesize evidence on the effectiveness of acupuncture and related therapies for primary carpal tunnel syndrome (CTS) by conducting a systematic review of randomized controlled trials (RCTs). Data Sources: Nine databases were searched for potential RCTs from their inception till July 2019. Review Methods: RCTs which reported at least one of the three outcomes were included: symptom severity, functional status and pain. Included RCTs were appraised using the Cochrane Risk of Bias Tool. Results: A total of 10 RCTs (728 participants) were included. Majority were at high risk of bias for blinding of participants, personnel and outcome assessors. When compared to conventional medications, manual acupuncture showed significant superior effect in reducing symptom than ibuprofen (mean difference (MD) on Symptom Severity Scale (SSS)) = –5.80, 95% confidence interval (CI): −7.95 to −3.65) and prednisolone (MD = −6.50, 95% CI: −10.1, −2.86). Electroacupuncture plus splinting was more effective in reducing symptom severity than splinting alone (SSS score: MD = −0.20, 95% CI: −0.36 to −0.03). Manual acupuncture showed significantly superior effect than ibuprofen in improving functional status (Functional Status Scale (FSS): MD = −1.84, 95% CI: −2.66 to −1.02). The combination of electroacupuncture and splinting showed more improvement in functional status compared to splinting alone (FSS: MD = −6.22, 95%CI: −10.7 to −1.71). Triple treatment of acupuncture, magnetic spectrum heat lamp and splinting showed stronger pain relief than splinting alone. Conclusion: For both symptom relief and function improvement, manual acupuncture is superior to ibuprofen while electroacupuncture plus splinting outperforms splinting alone. Limited evidence showed electroacupuncture's potential role in pain reduction.